Images and meaning analysing visual text in newspapers - Woodruff, Alan; Video Education Australasia (Bendigo , Vic.: Video Education Australasia, 1997)
Programme encourages students to develop their analytical skills in visual literacy, using The Age as a case study
Keywords: Newspapers -- Sections, columns, etc; Newspapers; Newspapers -- Illustrations